THE SPECIFICS OF A DANCE TEACHER’S WORK IN THE CRISIS OF 2020 - Jegere, Paula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The 2020 has been a year of many challenges in many professions and also for dance teachers. The daily challenge is to replace existing dance classes with a totally different class structure, which is defined by the governmental restrictions. The dance teachers must react to these restrictions immediately and without any methodological materials and support. In the crisis the dance teachers must use such learning organizational forms as: group, individual and online, and use them as alternatives to one another. Can a dance teacher reach their professional (curriculum) goals by alternating components of the study process? How do the changing circumstances affect dancers and their attendance? The aim of this article is to analyse the possibilities of a dance teacher to reach their professional goals with group, individual and online classes and to determine the dancers satisfaction with these classes. The research is realized in terms of one dance studio and in two stages. The first stage (March-July 2020) were an experimental video-instruction independent training analysis. 40 video materials were grouped in 20 classes and sent to 20 dancers. The second stage (September-January 2020) were group, individual and online class analysis from the teacher’s and dancers perspective. In the second stage 27 dancers and 5 dance teachers were surveyed.